Analysis of Regulations Regarding Interfaith Marriages According to a Religious Perspective, Marriage Law and Decision No. 916/Pdt.P/2022/Pn.Sby - Elrika, Elrika; Sudirman, Maman; Djaja, Benny (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2024)
Marriage in Indonesia is carried out by obtaining legal recognition from religion and the state. The Marriage Law stipulates that a legal marriage must follow the religious beliefs that are believed in. In Indonesia, the practice of interfaith marriage that is not allowed is Islam and Hinduism, while Catholicism and Protestantism, Buddhism and Confucianism are four religions that allow marriage with different religions. The Compilation of Islamic Law and SEMA dated January 30, 2019 number 231/ PAN/HK.0  1/2019 also regulates not recognizing interfaith marriages so that such marriages cannot be registered. However, Court Decision No. 916/Pdt.P 2022 /PN.Sby granted the applicants' request to legalize and register and record the marriage of the parties. Thus, for the parties who are married of different religions in the case. Have a valid marriage before the law and the state for interfaith marriages. However, in 2023, SEMA Number 2 of 2023 was issued on July 17, 2023 concerning Instructions for Judges in Adjudicating Cases of Applications for Marriage between People of Different Religions and Beliefs, which are prohibited from being granted by the court.